PENGARUH PREFERENSI MAHASISWA PROGRAM STUDI AKUNTANSI FAKULTAS EKONOMI UNIVERSITAS ISLAM BANDUNG (UNISBA) TERHADAP LOYALITAS DI BANK SYARIAH BANDUNG - Susilo Setiyawan; Epi Fitriah (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2013)
This study examined the strudents preferences toward syariah bank loyalities in the accounting department program of Bandung Islamic University. In addition, this research examine the validity, reliability and successive interval method on the variables. The research was conducted by cross-sectional basis. Analysis of the research conducted on 208 respondents. Respondents are students on accounting department program of Bandung Islamic University. This study applies OLS analytical tools. The results of the data analysis shows that students on accounting department program of Bandung Islamic University loyalities are positively and significantly influence toward Islamic banks in Bandung.